Alternative adjustment of scrotal circumference for growth traits in Nellore cattle - Nascimento, Barbara Mazetti; Silva, Gisele Ferreira da; Carvalheiro, Roberto [UNESP]; Teixeira, Rodrigo de Almeida; Dias, Laila Talarico (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
The objective of this study was to estimate adjustment factors of scrotal circumference for growth traits in Nellore cattle. Measurement at post-yearling of scrotal circumference from 100,107 Nellore was adjusted for six traits: age (A), body weight (BW), hip height (HH), conformation (C), precocity (P), musculature (M), and simultaneously for age and the other five traits (A-BW, A-HH, A-C, A-P, A-M), body weight and the other four traits (BW-HH, BW-C, BW-P, BW-M), and hip height and the other three traits (HH-C, HH-P, HH-M). Standard values were 500 days, 300 kg, 135 cm, and 3, for age, body weight, hip height, and visual scores, respectively. Amplitudes of adjustment factor of scrotal circumference for age, body weight, and hip height were 0.6028, 0.4869, and 0.1572, respectively. Scrotal circumference is expected to grow, on average, 8.71 cm per 100 days of age, 6.51 cm per 100 kg of body weight, and 4.81 cm per 10 cm of hip height. The results showed higher amplitude in the adjustment factor of scrotal circumference for age and body weight (0.3429) compared with age and hip height and body weight and hip height (0.1271 and 0.0443, respectively). The amplitude observed in adjustment factor of scrotal circumference for conformation, precocity, and musculature were 0.1328, 0.1175, and 0.1160, respectively. Considering different adjustment factors of scrotal circumference can be useful for identifying better selection criteria for growth and/or sexual precocity in Nellore.
Keywords: beef cattle; body weight; hip height; selection criteria; visual scores